Normothermic perfusion: a mini-review. - Reddy, S; Brockmann, J; Friend, P (2009)
The quality of organ preservation is critical to the outcome of transplantation: preservation technology is a limiting factor in the further development in the use of marginal donor organs. Normothermic preservation (preservation at normal physiological temperature) enables prolonged preservation, resuscitation after warm ischemia and organ viability assessment before transplantation.